Efisiensi Strategi Rantai Pasok Komoditas Cabai Merah (Efficiency of Red Chili Commodity Supply Chain Strategy) - Talitha Nariswari Nurjannah; Asti Permata Bunda; Purana Indrawan (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Chili (capsicum annum l.) is a crop that has high economic value and is widely cultivated in Indonesia. To ensure a stable and adequate supply of red chili, an efficient and well-organized supply chain management is needed, starting from farmers as the main producers to the final consumers. The purpose of the desk study is to determine the factors that affect the supply chain and the efficiency of the red chili supply chain improvement strategy. The method used uses the literature study method, namely by looking for data or information from various journals. From the results of the literature review, that the marketing of red chili commodities requires supply chain efficiency to improve performance and profits. One way to measure efficiency is through marketing margins, farmer's share, price, production, and marketing costs. This can be achieved by minimizing costs and maximizing added value in all supply chain activities